Abnormal percent amplitude of fluctuation changes in patients with monocular blindness: A resting-state functional magnetic resonance imaging study - Hu, Qiaohao; Chen, Jun; Kang, Min; Ying, Ping; Liao, Xulin; Zou, Jie; Su, Ting; Wang, Yixin; Wei, Hong; Shao, Yi (Frontiers in Psychiatry, 2022)
Purpose: Previous studies on monocular blindness (MB) have mainly focused on concept and impact. The present study measured spontaneous brain activity in MB patients using the percentage of amplitude fluctuation (PerAF) method. Methods: Twenty-nine patients with MB (21 male and 8 female) and 29 age-, gender-, and weight-matched healthy controls (HCs) were recruited. All participants underwent resting state functional magnetic resonance imaging (rs-fMRI). The PerAF method was used to analyze the data and evaluate the spontaneous regional brain activity. The ability of PerAF values to distinguish patients with MB from HCs was analyzed using receiver operating characteristic (ROC) curves, and correlation analysis was used to assess the relationship between PerAF values of brain regions and the Hospital Anxiety and Depression Scale (HADS) scores. Results: PerAF values in Occipital_Mid_L/ Occipital_Mid_R/ Cingulum_Mid_L were significantly lower in patients with MB than in controls. Conversely, values in the Frontal_Sup_Orb_L / Frontal_Inf_Orb_L/ Temporal_Inf_L/ Frontal_Inf_Oper_L were significantly higher in MB patients than in HCs. And the AUC of ROC curves were follows: 0.904, (p＜0.0001; 95% CI: 0.830-0.978) for Frontal_Sup_Orb_L/ Frontal_Inf_Orb_L; Temporal_Inf_L 0.883, (p＜0.0001; 95% CI: 0.794-0.972); Frontal_Inf_Oper_L 0.964, (p＜0.0001; 95% CI: 0.924-1.000), and 0.893 (p＜0.0001; 95% CI: 0.812-0.973) for Occipital_Mid_L; Occipital_Mid_R 0.887, (p＜0.0001; 95% CI: 0.802-0.971); Cingulum_Mid_L 0.855, (p＜0.0001; 95% CI: 0.750-0.960). Conclusion: The results of our study show abnormal activity in some brain regions in patients with MB, indicating that these patients may be at risk of disorder related to these brain regions. These results may reflect the neuropathological mechanisms of MB and facilitate early MB diagnoses.